Promenades. - Centre d'art contemporain, Genève (Genève : Centre d'Art Contemporain, 1985)
Acconci, Vito ; Ackling, Roger ; Armleder, John M. ; Bagnoli, Marco ; Boetti, Alighiero ; Defraoui Silvie et Chérif ; Dimitrijevic, Braco ; Fabro, Luciano ; Finlay, Ian Hamilton ; Horn, Rebecca ; Kirkeby, Per ; Kosuth, Joseph ; Mattner, Jakob ; etc.
Promenades, Parc Lullin, Genève, Centre d'Art Contemporain, Genève, 9 juin - 8 septembre 1985
boek